Trust of second generation immigrants: Intergenerational transmission or cultural assimilation? - Julie Moschion; Domenico Tabasso (Institute for the Study of Labor (IZA), 2013)
This paper studies the respective influence of intergenerational transmission and the environment in shaping individual trust. Focusing on second generation immigrants in Australia and the United States, we exploit the variation in the home and in the host country to separate the effect of the cultural background from that of the social and economic conditions on individual trust. Our results indicate that trust in the home country contributes to the trust of second generation immigrants in both host countries, but particularly so in the United States. Social and economic conditions in the host country, such as crime rate, economic inequality, race inequality and segregation by country of origin, also affect trust. Evidence for first generation immigrants confirms that the transmission of trust across generations is primarily important in the United States, and, that differences in trust levels between the two host countries increase with acculturation.
Keywords: J15; O15; Z10; 330; trust; migration; culture; Vertrauen; Migranten; Kulturelle Identität; Soziale Integration; Soziale Lage; Generationenbeziehungen; Australien; USA